Pengembangan Kreativitas Guru dalam Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Islam - Muttaqin, Muhammad Ridho (el Buhuth: Borneo Journal of Islamic Studies, 2020)
The background of the research is the creativity of the teacher in learning which is something that can help the learning process to maximize teaching and learning activities and also to facilitate the teacher to understand the material to students in Cordova Integrated Islamic Primary School, International Islamic School Balikpapan. This research is descriptive qualitative with the aim to find out how the creativity of teachers in learning Islamic religious education in Cordova School, SD INTIS SCHOOL, Informants of data in this study are the Principal, and two religious teachers divided into two, and also Administration that provides data school administration. The research uses data collection techniques that are divided among others: interviews, observation and documentation. Besides the research approach, the data analysis techniques used are Data Reduction (data reduction), Data Display (Data Presentation), and Conclusion Drawing (i.e. when the data presentation is complete, this stage is an analysis) then the validity of the data is tested. Based on the results of research on teacher creativity in learning Islamic education in the three schools, the authors found that Cordova always provided training to her teachers and made the teacher memorize the Qur'an, so that students could be helped by the creativity of the teacher in teaching the Qur'an. 's SD INTIS SCHOOL itself provides a large salary to teachers so that the enthusiasm of the teacher is certainly greater in the application of creativity in teaching. then, the teachers were financed by a higher level school as needed. speaker according to the desired needs. So that there is new things in creative learning.